Analogical Language and Religious Ritual in C. S. Lewis's "Till We Have Faces" - Little, Brent (Religion & literature, 2018)
Although C. S. Lewis remains beloved in the popular imagination, his last published work of fiction, Till We Have Faces: A Myth Retold (1956), is relatively little known. Unlike many of Lewis's more famous works, the book does not contain a clear argument for Christianity. But despite its ancient pagan setting and absence of explicit apologetics, Lewis's text invites theological reflection. For instance, its depictions of pagan rituals are essential to the story's thematic tapestry. In this article, I consider three pivotal scenes that provoke reflection on the symbolic language embodied in the story's religious rituals. In these scenes, Lewis, I argue, portrays language's capacity-- specifically the language of religious ritual and story--to articulate a reality beyond the limits of discourse, in short, a divine reality. This implies a faith in language itself, specifically in the analogical discourse, with its \"is\" and \"is not\" logic, that is fundamental to theJudeo-Christian tradition. The book's symbols imaginatively manifest the ambiguous nature of religious language. The reader thereby is provoked to wonder about one's faith in language itself: Can analogical language describe certain truths accurately, even if imperfectly?.